Penerapan Strategi Pembelajaran STAD (Student Teams Achievement Division) dalam Peningkatan Keterampilan Menulis Teks Eksplanasi pada Siswa Kelas XI SMAN 3 Parepare - Rabiah*, Sitti; Mazhu, Nurfathana; F.S, Tri Ramadhan (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
: Tri Ramadhan F. S. 2023. Application of STAD (Student Teams Achievement Division) Learning Strategy in Improving Explanatory Text Writing Skills in Class XI IPS 1 SMA 3 Parepare. Supervised by Dr. H. Sitti Rabiah, M. Hum. and Nurfathana Mazhud, S. Pd. M. Pd.This research aims to describe the process of implementing the STAD Strategy in learning explanatory texts, and to describe the results of writing explanatory texts. The focus of this research is Classroom Action Research (PTK). The data and data sources in this research are: 1) data on the process of learning activities and students' learning days using STDA strategy. 2) all students of class 11 IPS 1 SMA Negeri 3 Parepare totaling 20 students, consisting of 10 male students and 10 female students. The techniques used to obtain data were observation and test sheets. After the data was obtained, the data was then analyzed using qualitative descriptive techniques and quantitative analysis. This research was carried out over 2 cycles. The results of the first cycle of research showed that the average score was 60-75 with student learning activeness in the classroom achieved 65% and at the end of cycle II showed the average student learning score was 80 with student learning activeness in the classroom achievend 90%..Indonesian language learning keywords, Writing Explanatory Text, Strategy STAD.